MODERN TECHNOLOGY IN EDUCATION - Khalilova Shokhista Mukhammadi qizi; Turopova Shabbona Bxodir qizi (TADQIQOTLAR, 2026)
Abstract (English) This thesis examines the role of modern technology in contemporary education and its influence on teaching methodology, learner autonomy, and academic performance. The study analyzes digital learning environments, artificial intelligence, online educational platforms, and interactive technologies that contribute to the modernization of education systems. Comparative and pedagogical approaches are used to evaluate the advantages and limitations of technology-assisted learning. The paper also highlights the practical significance of digital literacy and technological integration in higher education institutions. The findings demonstrate that modern technology not only improves accessibility and communication but also enhances critical thinking, independent learning, and collaborative skills among students.